A Perspective on Synthesis and Applications of Fluorenones. Issue 34 (10th September 2020) - Patel, Sagarkumar; Rathod, Bhagyashri; Regu, Siddulu; Chak, Shivam; Shard, Amit
Abstract: Fluorenones are important constituents in material, medical and chemical sciences with potential applications in various domains. The key factors responsible for the diverse usage of fluorenones in material sciences are their intriguing and tunable photo, as well as physico‐chemical properties. Besides this, the presence of conjugated poly‐(en)ynes in the fluorenones makes them molecules of interest in material sciences. Fluorenones show various biological activities like antibiotics, anticancer, antiviral, and neuromodulatory, etc. Organic chemists are developing various protocols for the synthesis of fluorenones. Despite several protocols developed for their synthesis since 1931, there is no review covering their entire synthetic protocols. This review includes several classical and novel synthetic approaches for the synthesis of fluorenones. Furthermore, we delineated the mechanism by which they have been synthesized. Abstract : Fluorenones represent a class of compounds having applications from materials to medicine. They are used in material sciences like organic field‐effect transistors and organic electronic devices, whereas in medicinal chemistry domains they are employed as antibacterial, anticancer, antioxidant, neuromodulators, diuretics, and antivirals. This review highlights the most exciting examples of the fluorenone syntheses via intramolecular and intermolecular processes. Fluorenone synthesis using green as well as non‐green protocols is also discussed. The mechanism of reactions and future directions are also given.